2020
DOI: 10.3390/plants9081022
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Differentially Modulates Hypoxia Responses and Tolerance across Solanum Species

Abstract: The increasing occurrence of floods hinders agricultural crop production and threatens global food security. The majority of vegetable crops are highly sensitive to flooding and it is unclear how these plants use flooding signals to acclimate to impending oxygen deprivation (hypoxia). Previous research has shown that the early flooding signal ethylene augments hypoxia responses and improves survival in Arabidopsis. To unravel how cultivated and wild Solanum species integrate ethylene signaling to control subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
1
23
1
Order By: Relevance
“…Genes encoding plant cysteine oxidases (Solyc02g087740, Solyc03g113130, and Solyc10g007990) showed a significant transcriptional activation with no differences between genotypes, suggesting the activation of the N-degron pathway (Figure 6). It has been recently suggested that tomato ERFVIIs might be uncoupled from hypoxia-responsive gene induction (Hartman et al, 2020); nevertheless, our data indicate a clear correlation between the RAP2.2 ortholog and the expression of hypoxia-related transcripts. Interestingly, genes encoding known NO synthesis genes in plants, Solyc11g013810, encoding a nitrate reductase, and genes encoding for phytoglobins (Solyc08g068070 and Solyc07g008240), known for their ability to scavenge NO (Gupta et al, 2019), showed an upregulation in flooded tissues, with a larger fold change value in WT than in not.…”
Section: Discussioncontrasting
confidence: 70%
“…Genes encoding plant cysteine oxidases (Solyc02g087740, Solyc03g113130, and Solyc10g007990) showed a significant transcriptional activation with no differences between genotypes, suggesting the activation of the N-degron pathway (Figure 6). It has been recently suggested that tomato ERFVIIs might be uncoupled from hypoxia-responsive gene induction (Hartman et al, 2020); nevertheless, our data indicate a clear correlation between the RAP2.2 ortholog and the expression of hypoxia-related transcripts. Interestingly, genes encoding known NO synthesis genes in plants, Solyc11g013810, encoding a nitrate reductase, and genes encoding for phytoglobins (Solyc08g068070 and Solyc07g008240), known for their ability to scavenge NO (Gupta et al, 2019), showed an upregulation in flooded tissues, with a larger fold change value in WT than in not.…”
Section: Discussioncontrasting
confidence: 70%
“…Both of these nastic movements have been attributed to an altered ethylene metabolism, either by accumulation of ethylene gas due to diffusion barriers in water ( Sasidharan et al, 2017 ), or by upregulation of its biosynthesis pathway ( Bradford and Yang, 1980 ). Within the Solanaceae family, differentiation of epinasty in response to ethylene has been previously observed ( Edelman and Jones, 2014 ), as well as of their plasticity to waterlogging ( Hartman et al, 2020 ). Our results show that there indeed exists a differential responsiveness of species such as tomato, potato, and bell pepper to waterlogging, but also that leaf age plays a substantial role in this epinastic response ( Figures 4 and 6 ).…”
Section: Discussionmentioning
confidence: 96%
“…The occurrence of adventitious roots is one of the ways for plants to adapt to low oxygen stress in waterlogging [ 77 , 78 , 79 ]. H 2 S produced by microorganisms in soil is little absorbed by roots for its poor water solubility, and the main pathway of H 2 S accumulation is endogenous production in root cells.…”
Section: Adventitious Root Formation Photosynthesis Efficiency Improvement Cell Death Alleviation Promoted By H 2 S Agmentioning
confidence: 99%